The role of game-based learning in improving education and student learning - Abdukhalilovich Darmonov , Aliyorbek; Avliyakulova Nusratovna , Fotima; Ibrakhimovna Khamraeva , Gulchekhra; Elena Ivanovna , Popova; Ilkxamovna Nurmatova , Maftuna; Alina Vladimirovna , Xromenkova (Cadernos de Educação Tecnologia e Sociedade, 2024)
The purpose of this study was to investigate the role of educational games in increasing student learning. One of the new and innovative methods of education is the use of educational games in teaching, in which all students with any culture, intelligence level, and individual differences play it directly and with interest and motivation. By playing games, students can be taught the course and educational content indirectly and practically, and this learning is also deeper and more sustainable because students are interested in learning. This article examines the role of educational games and its importance and impact on student learning. The research method of this study was descriptive-analytical, which was investigated using library resources. The experimental group was affected by the independent variable of education through games, but the control group did not receive any intervention. The research tools used are the Learning Capabilities Questionnaire and the Learning Questionnaire. Finally, the data obtained from the research were analyzed using the univariate analysis of covariance using SPSS 16.0 software. The results of the analysis of covariance showed that game-based learning improved the learning of lesson concepts and increased interest in students (P>0.001). At the end of this study, the game teaching method and its advantages and disadvantages were examined.